La utilitas de la poesía en la retórica epicúrea: Fundamentos filosóficos de los beneficios de su sonoridad según Lucrecio - Mattos, Roberto Carlos (2022)
We discuss if the acknowledgement of the utility (utilitas) of poetry by Lucretius may be considered as an amplifying development of Epicurean rhetoric, a possibility yet to be investigated by current research trends. On the one hand, this task will consist in showing how Lucretius's proposal complies with the broad understanding of the act of persuasion and persuasive means, as outlined in extant Epicurean rhetoric. On the other, it will consist in establishing the compatibility between such proposal and the developments of Epicuren atomology and gnoseology.